2005
DOI: 10.1200/jco.2004.00.6361
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Helical Computed Tomography and [18F] Fluorodeoxyglucose Positron Emission Tomography for Identifying Lymph Node Mediastinal Metastases in Potentially Resectable Non–Small-Cell Lung Cancer

Abstract: hCT and PET perform similarly in the mediastinal staging of NSCLC, both tests are conditionally dependent and provide complementary information, and their diagnostic value mainly resides on the negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 26 publications
0
49
1
2
Order By: Relevance
“…Surgical specimens, study procedures, and clinical information of patients with potentially respectable non-small-cell lung cancer were those described previously (8). A summary of relevant clinicopathologic information of the cohort of patients analyzed is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical specimens, study procedures, and clinical information of patients with potentially respectable non-small-cell lung cancer were those described previously (8). A summary of relevant clinicopathologic information of the cohort of patients analyzed is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…PET examinations were done in 6-h-fasted patients using an ECAT EXACT 47 (Siemens-CTI) camera with whole-body attenuation (8). Patients entering the PET study had blood glucose concentrations <7 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…This ratio is reported as 16%-55% in the literature (9,11). In another study, it has been determined that not only the active inflammation, but also the healed or inactive pulmonary diseases (antecedent tuberculosis, silicosis, anthracosis) may potentially result in increased FDG capture in hilar or mediastinal lymph nodes (12). False positivity was determined in 34.6% of lymph nodes detected in PET/CT imaging in our study group.…”
Section: Discussionmentioning
confidence: 76%
“…Some of the studies that established very high sensitivities and negative predictive values of pet-ct in the mediastinum involved patients whose pet imaging was performed within 72 hours of surgery 25 . Mohammed et al 27 showed that clinical progression occurred in 21% of patients after 16 weeks' delay in surgery, and initially higher T and N stages were associated with more rapid progression.…”
Section: Discussionmentioning
confidence: 99%